Local Stability of Predator Prey Models With Harvesting On The Prey - Saiful Marom (Universitas Pekalongan, 2013)
In this paper considered the dynamics of a predator prey model with threshold harvesting on the prey. Theoretical and numerical methods are used to investigate boundedness of solutions, existence of equilibrium points, and the local stability of equilibrium points.